2021
DOI: 10.2500/aap.2021.42.200125
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in a patient with severe asthma using mepolizumab

Abstract: Background: There is a lack of information about the course of coronavirus disease 2019 (COVID-19) in patients with severe asthma who were treated with biologics. Some reports indicated that treatment with benralizumab, dupilumab, and omalizumab in patients with severe asthma was not associated with significant adverse effects during COVID-19.Methods: Asthma itself or the biologic agents used to treat asthma can have a positive effect on the course of COVID-19.There seem not to be any cases that specifically r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 10 publications
4
14
0
1
Order By: Relevance
“…However, a study conducted in the Netherlands revealed a poor outcome of COVID-19 in asthma patients treated with biologicals ( 51 ). Single case reports for asthma patients treated with Omalizumab ( 81 ), Mepolizumab ( 82 ) and Benralizumab ( 83 ) have been reported with a good outcome of COVID-19. Noticeably, a severe asthma patient treated with dupilumab presented with modest antibody response against SARS-CoV-2 ( 84 ), suggesting that further studies are needed to elucidate the safety of dupilumab during COVID-19.…”
Section: Asthma and Covid-19mentioning
confidence: 99%
“…However, a study conducted in the Netherlands revealed a poor outcome of COVID-19 in asthma patients treated with biologicals ( 51 ). Single case reports for asthma patients treated with Omalizumab ( 81 ), Mepolizumab ( 82 ) and Benralizumab ( 83 ) have been reported with a good outcome of COVID-19. Noticeably, a severe asthma patient treated with dupilumab presented with modest antibody response against SARS-CoV-2 ( 84 ), suggesting that further studies are needed to elucidate the safety of dupilumab during COVID-19.…”
Section: Asthma and Covid-19mentioning
confidence: 99%
“… 59 Aksu et al also reported the case of a COVID-19 severe asthma patient on mepolizumab who had mild disease. 60 Bhalla et al reported the case of a patient on dupilumab who had mild COVID-19. 61 …”
Section: Resultsmentioning
confidence: 99%
“…However, the results of some experimental infection models are difficult to align with observations of controlled studies of eosinophil-depleting anti-IL-5/5R biologics in humans, which do not appear to show increased rates of viral, bacterial, or helminth infections [5,6]. Moreover, although eosinopenia has been frequently observed in hospitalised patients with coronavirus disease 2019 (COVID-19) and has been linked to patient outcomes [32], emerging data indicate no increase in hospital admissions for COVID-19 amongst patients with asthma receiving eosinophil-depleting biologic therapies [33][34][35][36][37]. In fact, a potential beneficial effect in terms of a milder course of disease has been postulated for some patients.…”
Section: Physiologic Roles Of Eosinophilsmentioning
confidence: 99%